BIOTEKNOLOGI LINGKUNGAN UNTUK PENANGGULANGAN LIMBAH MENGANDUNG KROM - Dwi Andreas Santosa; Tommy Kurniawan; F. Dian Lina (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2008)
The biotechnological approaches for treatment of wastewater are widely studied within the last two decades. We show that this approach can be used for treatment of Cr-contaminated wastewater. The sulfate reducing bacteria Desulfotomaculum orientis ICBB 1204 is used in a laboratory experiment to treat Cr-contained wastewater from metal plating industry and the oil and gas company, PT VICO, East Kalimantan. After adaption of the bacteria for around 10 days in the wastewater containing 100 ppm Cr, the process of Cr reduction took place and the Cr in the medium were reduced 92.7% within 20 days. The similar results were achieved on the treatment of PT VICO’s wastewater. The Cr content in the wastewater decreased from 6.54-6.76 to 0.08-0.09 ppm and the pH increased from 3 to 5 – 6 within 20 days incubation period.Keywords: Cr detoxification, Desulfotomaculum orientis ICBB 1204, sulphate reducing bacteria, wastewater